"Maddie is online": an educational video cartoon series on digital literacy and resilience for children. Issue 1 (8th December 2020) - Martzoukou, Konstantina
Abstract : Purpose: This paper examines children's development of digital literacy, resilience and citizenship in the online environment, addressing active engagement and participation via cartoon videos. Previous research has emphasised the positive role of cartoons in different educational contexts, as important agents of attracting children's attention and interest with opportunities to engage in contextual and collaborative learning. Design/methodology/approach: The work describes the design and an initial pilot study of the animated cartoon video series, with a group of 30 children in an S1 class, at a secondary school in Scotland as part of workshop addressing digital resilience themes. Children worked individually and in teams in a series of interactive activities, which were evaluated by means of a short questionnaire survey. Findings: The majority of the children enjoyed the cartoon videos which addressed a story of cyberbullying and, in teams, they chose different copying strategies. Children's verbalisations included expressions of positive feelings when connecting online, linked to socialising, creative and playful activities and they expressed a preference towards speaking to their parents and friends rather than their teachers when dealing with online challenges. Research limitations/implications: Children not only enjoyed watching the cartoon story but had an interest to learn more about how other children deal with the pressures and challenges of the online world, how to manage their own digital footprint and, particularly, how easy it is to spread personal information online. Practical implications: Cartoon animations present an opportunity to act as a basis for encouraging children to exchange ideas and engage in dialogue in class and at home by means of creating a point of reference which creates an environment, where pressure is taken away from the "self". The cartoon character can be the focal point for discussion on issues that may be difficult to address directly and on a personal level because of insecurity or fear. Social implications: Both teachers and parents have a responsibility to offer support and advice to children and ensure their online safety and resilience. Engaging with children in open further dialogue via fun and interactive cartoon-based activities may help to further explore and understand their perspectives. Originality/value: The work addresses everyday life issues encountered online and aims to offer educators and parents an engaging and fun series of activities, harnessing the advantages of cartoon video animation as a didactical resource that can utilised as a supplementary learning tool inside the classroom and at home.